2016
DOI: 10.1111/ijfs.13068
|View full text |Cite
|
Sign up to set email alerts
|

Improved physical stability of docosahexaenoic acid and eicosapentaenoic acid encapsulated using nanoliposome containing α‐tocopherol

Abstract: This study aimed to develop a nanoliposomal formulation containing a-tocopherol loaded with eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) and to characterise the formulation by its physical stability. For this purpose, different nanoliposomal formulations with dipalmitoyl phosphocholine were prepared using a modified thin-film hydration method and evaluated by particle size, polydispersity index (PDI), transmission electron microscopy, differential scanning calorimetry and determining the encapsul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…They observed that the particle size of nanoliposomes was statistically stable especially in lower temperatures during storage for 3 months. Lipid oxidation during storage elevated by temperature, and the highest oxidation rate observed was at 40 • C. Although, a high level of EPA and DHA was degraded during storage of nanoliposomes, but the addition of alpha-tocopherol limited EPA and DHA decomposition due to its antioxidant effect, which was more significant for samples stored at 4 • C. These researchers concluded that dual encapsulation of DHA/EPA into antioxidant-containing nanoliposomes can significantly improve the health benefits of food products [130].…”
Section: Encapsulation Of Essential Fatty Acids and Essential Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed that the particle size of nanoliposomes was statistically stable especially in lower temperatures during storage for 3 months. Lipid oxidation during storage elevated by temperature, and the highest oxidation rate observed was at 40 • C. Although, a high level of EPA and DHA was degraded during storage of nanoliposomes, but the addition of alpha-tocopherol limited EPA and DHA decomposition due to its antioxidant effect, which was more significant for samples stored at 4 • C. These researchers concluded that dual encapsulation of DHA/EPA into antioxidant-containing nanoliposomes can significantly improve the health benefits of food products [130].…”
Section: Encapsulation Of Essential Fatty Acids and Essential Oilsmentioning
confidence: 99%
“…Sahari and coworkers [130] developed nanoliposomes containing DHA and EPA with or without alpha-tocopherol. They observed that the particle size of nanoliposomes was statistically stable especially in lower temperatures during storage for 3 months.…”
Section: Encapsulation Of Essential Fatty Acids and Essential Oilsmentioning
confidence: 99%
“…Tuna eyeball oil had DHA as the dominant LCPUFAs (Renuka et al ., 2016; Pudtikajorn & Benjakul, 2020). However, during processing or extraction, the high susceptibility of DHA and EPA to oxidation can lead to rapid deterioration (Sahari et al ., 2016). The auto‐oxidation of LCPUFAs is mainly related to free radical formation, generated by heat, radiant, trace metals and enzymes (Zuta et al ., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Rasti et al investigated the encapsulation of DHA and EPA in ~300–350 nm diameter liposomes and observed that a preparation method involving aqueous solvent only yielded greater oxidative stability compared to a preparation method that involved aqueous and organic solvents [ 84 ]. Further refinements of the liposomal formulation included α-tocopherol, which enhanced oxidative protection to increase stability [ 85 , 86 ].…”
Section: Application Examplesmentioning
confidence: 99%